Socialization And Training Of Web-Based Cendana Posyandu Information System In Kahuripan Village, Tasikmalaya City - Hani Rubiani; Eddy Samsoleh; Sulidar Fitri; Shofia Rahmah Soprani (AbdimasMu UMTAS, 2022)
Information system is an integrated system that provides information or data to support various operational activities, management, and decision-making functions of an organization or company. Information systems are needed in an organization because what determines the running of an organization is the information it has, such as in making reports given to the leadership, depending on whether the information is accurate or not. As is the case in non-profit organizations in the community, namely Posyandu. Posyandu (Pos Pelayanan Terpadu) is a form of Upaya Kesehatan Bersumberdaya Masyarakat (UKBM) carried out by, from and with the community, to empower and provide convenience to the community to obtain health services for mothers, infants and toddlers. The implementation of the Posyandu which is routinely carried out every month is carried out by health cadres whose workforce is voluntary and is chosen by local residents and is tasked with fostering the community. The purpose of this community service program is to provide knowledge and understanding to Posyandu cadres so that they can provide maximum health services to the community, especially health service administration during registration, recording and reporting, namely by providing socialization of the use of the Web-Based Posyandu Information System for Cendana Posyandu cadres in Kahuripan Village, Tasikmalaya City. It is hoped that with this socialization, the cadres can use the Posyandu Information System properly so that the health services provided can run optimally. Features that exist in the Posyandu Information System include recording of mother's d